ENHANCED PERCUTANEOUS PERMEABILITY OF ACYCLOVIR BY DMSO FROM TOPICAL GEL FORMULATION (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
The aim of this study was to investigate the effect of DMSO on the permeation of acyclovir in the form of topical gel formulations. Different formulations were prepared containing carbopol 934P, acyclovir (1 % w/w) and selected concentration of DMSO (0 to 10% w/w) to evaluate drug content, spreadibility, pH, viscosity, and in-vitro permeation through mouse epidermis and porcine skin. FTIR spectrometry was used to investigate physical state of drug in the gel formulations. The mechanisms of drug permeation were evaluated by FTIR spectrophotometer and histopathological studies. The carbopol 934P gel was found to contain 95.62 to 98.89 % of acyclovir and spreadibility was found in the range of 10.75 to 11.75 g.cm/sec. The pH of all formulations was found near to the skin pH value. The viscosity of the formulations was found inversely proportional with drug permeation. A maximum permeation flux of acyclovir (463.42±36.41µg/cm2.h) through porcine skin was observed with an enhancement ratio of 1.55, when DMSO was incorporated at a concentration of 10%w/w in gel system. The FTIR spectra revealed the absence of drug-polymer interaction. From FTIR spectroscopy and histopathological studies it was evident that the permeation of acyclovir, across mouse and porcine skin, were increased in presence of DMSO which can be attributed to the partial extraction of lipids in the stratum corneum. The results suggest that DMSO may be useful for enhancing the skin permeability of acyclovir from transdermal therapeutic system containing carbopol 934P gel as reservoir.